Quality Management in Libraries Case Study: Book Collection Retrieval in Academic Libraries - Vilianty Rizki Utami; Desni Sri Hastuti Sihite (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
Quality management in the library is related to quality control of the library's work to meet user expectations and contributes to the continued success of the organization. However, quality control is lacking and not be the main focus in many libraries. This paper aims to explain how quality management improves work results in libraries. The research method used in this paper is qualitative research using a case study method. We conduct research in Library X that already underwent quality control in book processing activities. The data were collected through observation, and interviews for book processing activities and its quality control data during 2018-2020. The data was then analyzed document analysis. The study found that Library X could perform better by improving the quality of book processing and fixing the error just before they put the book on its shelves. Quality control gives a comprehensive evaluation in Library X either for humans, processes, and systems of book processing activities that help Library X conduct its duty to provide their user needs and expectations. Quality control and quality management also help Library X describe the library working atmosphere and can be used for giving motivation to all librarians and staff to give better service and performance for the end-users.